THU0512 HEALTH RISK BEHAVIORS IN ADOLESCENTS WITH JUVENILE IDIOPATHIC ARTHRITIS (JIA) IN THE COURSE OF DISEASE: RESULTS OF THE GERMAN MULTICENTER INCEPTION COHORT (ICON). (2nd June 2020) - Milatz, F.; Liedmann, I.; Niewerth, M.; Klotsche, J.; Horneff, G.; Weller-Heinemann, F.; Foeldvari, I.; Windschall, D.; Minden, K.
Abstract : Background: Health risk behaviors (HRB) are defined as specific forms of behavior associated with increased susceptibility to a specific disease or ill health on the basis of epidemiological or social data. The social implications of HRB include being able to use them as a way to gain respect and acceptance from peers, establishing independence from parents, or providing a subjective feeling of maturity and adequate stress management [1]. Objectives: Since chronically ill adolescents such as those suffering from JIA can develop a HRB that is challenging for optimal care the aim of this study was to compare the frequency of HRB in adolescents with JIA and their peers, and to determine whether they change during the course of disease. Methods: Patients ≤ 16 years of age with recently diagnosed JIA (< 12 months) were enrolled in the inception cohort of patients with newly diagnosed JIA (ICON), an ongoing prospective observational, controlled multicenter study started in 2010. Patients from the age of 13 who were questioned about their health behavior and followed up for at least 2 years were selected. HRB were quantified and compared with those of subjects from the general population after matching for age and sex. Data from 2-year follow-up (FU) were used to analyze correlates of multiple risk behavior defined as involvement in two or more risky behaviors. Results: A total of 209 adolescents with JIA (63% female, mean age at baseline 14.4±0.9, mean disease duration 2.6±2.0) and 138 healthy peers (55% female, mean age 14.5±1.0) were included. At baseline, 51% of patients were treated with a DMARD, 21% with a biologic (FU: 59% and 38%). The most common JIA category was rheumatoid factor negative polyarthritis (28%). While at baseline 20% of patients and 4% of controls did not engage in regular physical activity, the proportion at follow-up amounted to 16% and 10%, respectively (OR 3.69; 95%CI: 1.01-13.50). In both groups the proportion of regular smokers, alcohol consumers and drug users increased during the observation period. Significant group differences were found in terms of alcohol consumption and smoking habits, but not in relation to illicit and legal drugs (see table ). Patients stated significantly more often that they had not used a condom during their last sexual intercourse (28% vs. 19% controls, p<0.05). Multiple risk behavior was associated with PedsQL™ total score (OR 0.96; 95%CI: 0.92-0.99) and disease duration (OR 0.75; 95%CI: 0.57-0.98). Conclusion: Although adolescents with JIA became more physically active during the course of the disease, they are as likely, or more likely, to take risky behaviors than their healthy peers, except for alcohol consumption. In order to achieve optimal outcomes, addressing emotional wellbeing and providing mandatory anticipatory guidance appears to be warranted in this population. References: [1]Villarreal-Rodriguez D et al. Adolescents with chronic disease and participation in risky behaviors. Medicina Universitaria 2013;15(58):21–25. Acknowledgments: ICON is supported by a grant from the German Federal Ministry of Education and Research (FKZ 01 ER 1504A) Disclosure of Interests: Florian Milatz: None declared, Ina Liedmann: None declared, Martina Niewerth: None declared, Jens Klotsche: None declared, Gerd Horneff Grant/research support from: AbbVie, Chugai, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Speakers bureau: AbbVie, Bayer, Chugai, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Frank Weller-Heinemann: None declared, Ivan Foeldvari Consultant of: Novartis, Daniel Windschall: None declared, Kirsten Minden Consultant of: GlaxoSmithKline, Sanofi, Speakers bureau: Roche